IDENTIFIKASI JENIS TELUR NEMATODA USUS GOLONGAN Soil Transmitted Helminth (STH) DI KAWASAN PASIR PANTAI KECAMATAN SEKUPANG KOTA BATAM - Deasy Ovi Harsachatri; Raden Muhamad Taupik; Nurlaili Nurlaili; Mifthahul Jannah (CV. ALIM'SPUBLISHING, 2024)
. Soil Transmitted Helminth (STH) is a group of intestinal nematode worms that require soil for the maturation process so that there is a change from a non-infective stage to an infective stage. This study aims to find out whether in the coastal sand area of Sekupang District, Batam City, there are intestinal nematode eggs of the Soil Transmitted Helminth (STH) group. The method used in this study is a survey method by taking sand samples from 3 different beaches, namely Tanjung Pinggir beach, Dangas beach, and Marina beach, then the sample is examined, namely by soaking the sample with 15 ml of saturated NaCl for 30 minutes stirring until evenly distributed with a stirring rod then transferred the soaking water in a test tube. Deck glass is placed on top at the mouth of the tube for 60 minutes. Then the sample was observed under a microscope with a magnification of 10 to 40 then analyzed descriptively by making a picture systematically. The results showed that there were no intestinal nematode worm eggs of the STH group in the beach sand sample so that it could be concluded that the tannjung beach sand area of Sekupang District, Batam City was free from contamination of intestinal nematode worm eggs of the soil transmitted helmith (STH) group.